5x-3(-1)=39

Simple and best practice solution for 5x-3(-1)=39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(-1)=39 equation:


Simplifying
5x + -3(-1) = 39

Multiply -3 * -1
5x + 3 = 39

Reorder the terms:
3 + 5x = 39

Solving
3 + 5x = 39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 5x = 39 + -3

Combine like terms: 3 + -3 = 0
0 + 5x = 39 + -3
5x = 39 + -3

Combine like terms: 39 + -3 = 36
5x = 36

Divide each side by '5'.
x = 7.2

Simplifying
x = 7.2

See similar equations:

| 6(x+2)=4(x+20) | | (180-x)+35=90 | | p=r+s-7 | | -11(3m-9n+2p)= | | 3x+16=x+52 | | -x^2+x-3=0 | | 2x^3-23x^2+25x+50=0 | | 8+6w=160 | | -4(4y-6)+3(3y+8)= | | 5t+8(1.8-t)=12 | | 180=x+55+90 | | 5t+12(1.8-t)=8 | | -9x+5=x-3 | | -5z-12+20z=-11.4+15.6z | | 5(x+6)=3(x+14) | | 180-x=35+90+35 | | 25y^4+20y^2+3=0 | | 5y^4-7y^2-24=0 | | 10x+20=3x | | a^4+64a^2+63=0 | | n+27=-45 | | 14.62+0.07x=15.12-0.09 | | -9(x+4)+2x+5=8x+7 | | 12x-6=-40 | | 14+27x=35+20x | | 4x-12+x=4x-1 | | -4(2t+6)=-40 | | 4(f-4)=-36 | | 15x^2-2-7x=0 | | x+2=97 | | 8(x+1)=4+x | | 10(s-8)=-158 |

Equations solver categories